2010
DOI: 10.1590/s1516-05722010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Espaçamentos entre plantas e cobertura do solo com cama-de-frango na produção da bardana (Arctium lappa L.)

Abstract: RESUMO:O objetivo do trabalho foi estudar o crescimento, o desenvolvimento e a produção da bardana em resposta a cinco espaçamentos entre plantas (40,0; 47,5; 55,0; 62,5 e 70,0 cm) e ao uso (CCF) ou não (SCF) de cobertura de solo com cama-de-frango semidecomposta. Os dez tratamentos foram arranjados como fatorial 5x2, no delineamento experimental blocos casualizados, com quatro repetições. As plantas foram propagadas inicialmente em berços de isopor e, posteriormente, em canteiros, arranjadas em fileiras dupla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This provides higher plants per unit area in the smaller spacing, with better interception of solar radiation, higher photosynthesis rate and among other factors, which consequently increase the efficiency of water and soil nutrient uptake (Taiz and Zeiger, 2004). Munarin et al (2010) did not observe significant interaction between spacings and soil cover with chicken litter, working with the medicinal burdock species (Arctium lappa L.). However, they affirm that the smaller spacing (0.40 m) influenced the increase of the fresh matter production of the plants, because in smaller spacings, the metabolic processes of the plants became more efficient, favoring the best use of the resources in the environment.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This provides higher plants per unit area in the smaller spacing, with better interception of solar radiation, higher photosynthesis rate and among other factors, which consequently increase the efficiency of water and soil nutrient uptake (Taiz and Zeiger, 2004). Munarin et al (2010) did not observe significant interaction between spacings and soil cover with chicken litter, working with the medicinal burdock species (Arctium lappa L.). However, they affirm that the smaller spacing (0.40 m) influenced the increase of the fresh matter production of the plants, because in smaller spacings, the metabolic processes of the plants became more efficient, favoring the best use of the resources in the environment.…”
Section: Resultsmentioning
confidence: 69%
“…The averages followed by the same letter do not differ by the F test (p ≤ 0.01). Munarin et al (2010) observed that the smaller spacing for burdock plants (0.40 cm) resulted in higher leaf dry mass production. The authors suggest that probably the plants did not reach population pressure that would reduce their total productive capacity, due to competition for growth factors such as photosynthetically active solar radiation, water and nutrients, which would promote a decrease in the productivity of cultivated plants.…”
Section: Resultsmentioning
confidence: 95%
“…Among several officinal plants, Burdock ( Arctium lappa L.), Dandelion ( Taraxacum officinale ), and Lemon balm (Melissa officinalis ) have been used for their edible and medicinal properties [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%